A pilot study of a Community Health Agent-led type 2 diabetes self-management program using Motivational Interviewing-based approaches in a public primary care center in São Paulo, Brazil. Issue 1 (December 2017) - do Valle Nascimento, Thais; Resnicow, Ken; Nery, Marcia; Brentani, Alexandra; Kaselitz, Elizabeth; Agrawal, Pooja; Mand, Simanjit; Heisler, Michele
Abstract Background Rates of noncommunicable diseases (NCDs) such as type 2 diabetes are escalating in low and middle-income countries such as Brazil. Scalable primary care-based interventions are needed to improve self-management and clinical outcomes of adults with diabetes. This pilot study examines the feasibility, acceptability, and outcomes of training community health agents (CHAs) in Motivational Interviewing (MI)-based counseling for patients with poorly controlled diabetes in a primary care center in São Paulo, Brazil. Methods Nineteen salaried CHAs participated in 32 h of training in MI and behavioral action planning. With support from booster training sessions, they used these skills in their regular monthly home visits over a 6 month period with 57 diabetes patients with baseline HbA1cs > 7.0%. The primary outcome was patients' reports of the quality of diabetes care as measured by the Portuguese version of the Patient Assessment of Chronic Illness Care (PACIC) scale. Secondary outcomes included changes in patients' reported diabetes self-management behaviors and in A1c, blood pressure, cholesterol and triglycerides. We also examined CHAs' fidelity to and experiences with the intervention. Results Patients reported improvements over the 6 month period in quality of diabetes care received (PACIC score improved 33 (+/−19) to 68 (+/−21) (p < .001)). They reported increases in physical activity (p = .001), consumption of fruits and vegetables (p < .001) and medication adherence (p = .002), but no decreases in consumption of high-fat foods (p = .402) or sweets (p = .436). Participants had mean 6-month A1c levels 0.34% points lower than at baseline (p = .08) and improved mean LDL (−16.1 mg/dL, p = .005) and triglyceride levels (−38.725 mg/dL, p = .002). Of the 16 CHAs observed in fidelity assessments, 13 were categorized as medium- or high-performing on MI skills, while 3 were low-performing. CHAs expressed enthusiasm about learning new skills, and many described a shift from advice-giving to encouraging patients to define their own goals. Conclusion In resource-scarce settings, it is essential to fully utilize existing primary care resources to stem the epidemic of diabetes and other NCDs. Our pilot results support the potential of training CHAs to incorporate effective diabetes self-management support into their routine patient encounters. Trial registration NCT02994095 12/14/2016 Registered retrospectively.